2017
DOI: 10.3906/vet-1602-11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different processing methods of pigeon pea (Cajanus cajan) on growth performance, carcass traits, and blood biochemical and hematological parametersof broiler chickens

Abstract: This has encouraged improved effort at finding cheaper alternatives to prolong the production of poultry and maximize the potentials of the improved poultry strains available, at a reasonable cost. Pp is an important grain legume commonly grown and consumed in both tropical and subtropical regions of the world. It is also known as "lobiaadassy" (6). According to Saxena (7) the area cultivated has jumped to over 4.92 × 10 6 ha. It is considered a multipurpose nitrogen-fixing plant that provides food, fuel wood,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…Although, Furlan et al (2004) had earlier concluded that nutritional composition, especially the class of amino acids, the monomeric unit of protein in the feed, was interconnected with the building of structural tissues. Arif et al (2017) observed that feeding a 20% potash-boiled pigeon pea seed meal diet favoured carcass and breast weight, which is not similar to this study in which breast yield peaked at 12.50% compared to those fed 37.50%. Ojediran et al (2016a) demonstrated that thigh weight was influenced by the lysine portion of the feed.…”
Section: The Histological Observation Of the Livercontrasting
confidence: 99%
“…Although, Furlan et al (2004) had earlier concluded that nutritional composition, especially the class of amino acids, the monomeric unit of protein in the feed, was interconnected with the building of structural tissues. Arif et al (2017) observed that feeding a 20% potash-boiled pigeon pea seed meal diet favoured carcass and breast weight, which is not similar to this study in which breast yield peaked at 12.50% compared to those fed 37.50%. Ojediran et al (2016a) demonstrated that thigh weight was influenced by the lysine portion of the feed.…”
Section: The Histological Observation Of the Livercontrasting
confidence: 99%
“…Montilla et al [44] reported that feeding laying hens with sun-dried Gliricidia sepium resulted in better performance than those fed with the oven-dried legumes, but the effects of type of drying are not clear on the feed quality. Thermal management significantly reduced the trypsin-inhibitory activity of seeds of Cajanus cajan [45,46], Glycine max [47], Psophocarpus tetragonolobus [48], and Arachis hypogaea [49].…”
Section: Heat Treatmentsmentioning
confidence: 99%
“…Pigeon pea (Cajanus cajan) are highly nutritious, contains crude protein (CP) of 22%-27 and also crude fiber (CF) of 7.3%-10%, nitrogen-free extract (NFE) of 61.2%, ether extract (EE) of 1.7%-2.1%, ash of 3.1%-4.2%, and lysine of about 7.59% [7,8] and essential amino acids such as methionine, lysine and tryptophan [9,10]. It is a fast growing, hardy, widely adaptable and drought resistant crop and it is an important grain legume commonly grown and consumed in both tropical and subtropical regions and could be a better and cheaper protein alternative as compared to other legume grains [11,8].…”
Section: Introductionmentioning
confidence: 99%
“…Pigeon pea (Cajanus cajan) are highly nutritious, contains crude protein (CP) of 22%-27 and also crude fiber (CF) of 7.3%-10%, nitrogen-free extract (NFE) of 61.2%, ether extract (EE) of 1.7%-2.1%, ash of 3.1%-4.2%, and lysine of about 7.59% [7,8] and essential amino acids such as methionine, lysine and tryptophan [9,10]. It is a fast growing, hardy, widely adaptable and drought resistant crop and it is an important grain legume commonly grown and consumed in both tropical and subtropical regions and could be a better and cheaper protein alternative as compared to other legume grains [11,8]. However, like other legumes, there are some antinutritional factors such as trypsin and chymotrypsin inhibitors regarding the use of pigeon pea as a feed ingredient in poultry feeding [12] but different processing methods, such as boiling, crushing, soaking, roasting etc., have been employed to inactivate the antinutrients in pigeon pea [13].…”
Section: Introductionmentioning
confidence: 99%